1971
DOI: 10.2337/diab.20.6.416
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Delay in the Plasma Insulin Response of Patients with Chemical Diabetes Mellitus?

Abstract: We have compared the plasma glucose and immunoreactive insulin responses to oral glucose, intravenous glucose and intravenous tolbutamide of twenty normal subjects with those of eleven patients with chemical diabetes. The two groups were similar in terms of age, sex and degree of adiposity. The insulin response of patients with chemical diabetes was greater at every time interval during all these tests. Thus, we could document no defect in the rapidity of insulin response to these stimuli in patients with chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Perley and Kipnis (2) and Bagdade et al (3) observed a decreased insulin response to glucose in nonobese as well as obese subjects with maturity-onset diabetes when compared with weight-matched controls. On the other hand, Reaven et al (4,5) and other workers (6-8) have reported normal or increased insulin levels in maturity-onset diabetes, thus suggesting a role for insulin resistance in the pathogenesis of this disorder.…”
Section: Introductionmentioning
confidence: 95%
“…Perley and Kipnis (2) and Bagdade et al (3) observed a decreased insulin response to glucose in nonobese as well as obese subjects with maturity-onset diabetes when compared with weight-matched controls. On the other hand, Reaven et al (4,5) and other workers (6-8) have reported normal or increased insulin levels in maturity-onset diabetes, thus suggesting a role for insulin resistance in the pathogenesis of this disorder.…”
Section: Introductionmentioning
confidence: 95%
“…However, Perley and Kipnis (1967) reported that insulin response to glucose was decreased in diabetic patients in comparison with non-diabetic people from the experiment in which the pattern of blood glucose curves was simulated each other by glucose infusion in diabetes and non-diabetic subjects. To the contrary, Chiles and Tzagournis (1970) and Reaven et al (1971) observed an excessive response of plasma insulin to glucose in mild diabetes. Seltzer et al (1967) reported the delayed hyperinsulinemia in mild diabetics.…”
Section: Discussionmentioning
confidence: 94%
“…Since the fasting level of plasma insulin in diabetes mellitus is not different from that of normal subjects Ohneda 1966), glucose loading has been widely applied by many investigators in the study of the insulin secretion. However, the results are conflicting: Several authors reported the subnormal response of serum insulin to glucose in mild diabetes (Perley and Kipnis 1967;Floyd et al 1968), while others observed an excessive insulin response to glucose (Chiles and Tzagournis 1970;Reaven et al 1971). …”
mentioning
confidence: 99%
“…However, at least one extremely important distinction exists between patients with chemical diabetes and those with significant fasting hyperglycemia, and this relates to their insulin response to a glucose challenge. Thus, the insulin response of patients with chemical diabetes is equal to or greater than normal (9)(10)(11)(12)(13). In these patients it seems reasonable to suggest that hyperglycemia is secondary to insulin resistance, and the exaggerated insulin response can be viewed as a compensatory mechanism aimed at minimizing glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%